1989
DOI: 10.1111/j.1471-4159.1989.tb02549.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐Evoked Ca2+ Mobilisation and Prostanoid Release from Astrocytes: P2‐Purinergic Receptors Linked to Phosphoinositide Hydrolysis

Abstract: Astrocyte cultures prelabelled with either [3H]inositol or 45Ca2+ were exposed to ATP and its hydrolysis products. ATP and ADP, but not AMP and adenosine, produced increases in the accumulation of intracellular 3H-labelled inositol phosphates (IP), efflux of 45Ca2+, and release of thromboxane A2 (TXA2). Whereas ATP-stimulated 3H-IP accumulation was unaffected, its ability to promote TXA2 release was markedly reduced by mepacrine, an inhibitor of phospholipase A2 (PLA2). ATP-evoked 3H-IP production was also spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 33 publications
6
80
0
Order By: Relevance
“…The number of HA-tagged wild-type P2Y 2 receptors in 1321N1 cells was estimated by comparison with the fluorescence intensity due to HA-tagged ␤ 2 -adrenergic receptors (500 fmol/mg of total protein) in HEK-293 cells (20). The ␤ 2 -adrenergic receptor density was determined to be 32,667 Ϯ 6692 receptors/cell compared with 22,767 Ϯ 9753 receptors/cell for the wild-type P2Y 2 receptor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of HA-tagged wild-type P2Y 2 receptors in 1321N1 cells was estimated by comparison with the fluorescence intensity due to HA-tagged ␤ 2 -adrenergic receptors (500 fmol/mg of total protein) in HEK-293 cells (20). The ␤ 2 -adrenergic receptor density was determined to be 32,667 Ϯ 6692 receptors/cell compared with 22,767 Ϯ 9753 receptors/cell for the wild-type P2Y 2 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that, during our experiments, too much UTP and too few 1321N1 cells were present to demonstrate significant hydrolysis of nucleotide. P2Y 2 Receptor Sequestration Is Reversible-The reversibility of sequestration of the wild-type P2Y 2 receptor was determined after preincubating cells for 10 min with 1 mM UTP. Following incubation of the cells for various times in the absence of agonist, cell-surface receptor expression was determined.…”
Section: Progressive Truncations Of the C Terminus Results In Alteredmentioning
confidence: 99%
See 2 more Smart Citations
“…40 -42 Subsequent in vitro experiments have demonstrated that glial cells express the very same diverse variety of neurotransmitter receptors and ion channels as do neurons, [43][44][45][46][47][48][49][50][51][52][53][54][55] thus raising the question of the role for neuroglia in information processing in the brain. Further experiments have found that the expression pattern of neurotransmitter receptors in situ is very much restricted by the immediate neurotransmitter environment; as a consequence glial cells are properly endowed to sense the neurotransmitters released in their territorial domains.…”
Section: Signaling In Neuronal-glial Circuits 1) Glial Cells Express mentioning
confidence: 99%